PENGEMBANGAN MODUL PEMBELAJARAN KIMIA BERBASIS MODEL PERUBAHAN KONSEPTUAL ED3U (EXPLORE, DIAGNOSE, DESIGN, DISCUSS, USE) TERINTEGRASI MULTI REPRESENTASI PADA MATERI STRUKTUR ATOM - Zonalia Fitriza; Fauzana Gazali (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
This research aims to produce a valid chemistry module based conceptual change model Explore, Diagnose, Design, Discuss and Use (ED3U). The steps of this model are align with scientific approach which is an approach used in current curriculum. This model make the student find their own conception and considering their prior conception will resist or they need alternative conception so that they can have scientific conception. In order to optimalize this, the module is presented using three level chemistry representations that are macroscopic, submicroscopic and symbolic. Developments of this module used 4-D model (define, design, develop, disseminate) with check list as a non test instrument for observation in define step. Beside, it also use questioner to determine whether the module is valid or not. The data was analyzed by Kappa Cohen Formula. Based on the three validators who are the chemistry education lecturers and two validators who are lecturers of Design Communication Visual found that the value of k is 0,829 for content validation and 0,69 for graphics validation. It means the module is valid in high category.